2019
DOI: 10.3390/agronomy9110691
|View full text |Cite
|
Sign up to set email alerts
|

Production Indicators in Cowpea as a Function of the Water–Fertiliser Nexus

Abstract: The bean is an important crop in feeding the global population. In the northeast of Brazil, it is of particular importance, since it is a staple food, which also generates employment and income. The low productivity of the northeast in recent years due to the water crisis combined with the cost of energy has compromised technical and economic viability. This study aimed to evaluate production parameters of cowpea (Vigna unguiculata (L.) Walp.) under different alternative production systems in the northeast of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Research also shows domestic sewage contains enough nutrients to replace mineral fertilizers in cowpea production. Thus, previous studies have shown that fertilization with domestic effluents positively affects cowpeas' agronomic characteristics (FEITOSA et al, 2019;FERREIRA et al, 2019). However, it should be noted that in these studies, the application of domestic effluent began after seed germination.…”
Section: Introductionmentioning
confidence: 90%
“…Research also shows domestic sewage contains enough nutrients to replace mineral fertilizers in cowpea production. Thus, previous studies have shown that fertilization with domestic effluents positively affects cowpeas' agronomic characteristics (FEITOSA et al, 2019;FERREIRA et al, 2019). However, it should be noted that in these studies, the application of domestic effluent began after seed germination.…”
Section: Introductionmentioning
confidence: 90%